Identification of Facebook features supporting intrinsic motivations of senior entrepreneurs / Marlina Muhamad ... [et al.] - Muhamad, Marlina; Jamaludin, Mohd Fazil; Mohd Hardi, Norafiza; Abd Razak, Fariza Hanis; Haron, Haryani (Universiti Teknologi MARA, Kedah, 2023)
Senior entrepreneurs are different from young entrepreneurs because their main motivation to become entrepreneurs after retirement is mostly dominated by intrinsic values. To support extrinsic motivation like financial rewards and wealth creation, past studies have agreed that social media platforms are widely used by entrepreneurs. As social media adoption helpfully supports most entrepreneurs, this leaves some spaces to be explored and requires further research, especially on senior entrepreneurs since their primary motives are dominated largely by intrinsic motivations. Senior entrepreneurs are associated with lower technical skills; thus, the use of information and communications technology (ICT) becomes a challenge for them. This underexplored study offers a significant area of study as a caused from an increment in ageing population worldwide. This qualitative study applied in-depth semistructured interview with ten participants to understand the senior entrepreneurs’ motivations. Next, in identifying suitable Facebook features to support senior entrepreneurs’ intrinsic motivations, expert interviews were conducted with five experts in social media platforms. The four categories of motivations known as economic self-interest, social affirmation, active aging, and independence identified in this study confirmed that senior entrepreneurs are inclined toward intrinsic motivations. The findings further disclose senior entrepreneurs using social media such as Facebook, yet, many features could still be explored through this platform. The Facebook features identified from the expert interviews were mapped with senior entrepreneurs’ intrinsic motivations.